Aza-Henry and aza-Knoevenagel reactions of nitriles for the synthesis of pyrido[1, 2-a]indoles. Issue 48 (12th May 2020) - Zalte, Rajesh R.; Festa, Alexey A.; Golantsov, Nikita E.; Subramani, Karthikeyan; Rybakov, Victor B.; Varlamov, Alexey V.; Luque, Rafael; Voskressensky, Leonid G.
Abstract : N -(Propargyl)indole-2-carbonitriles undergo DBU-catalyzed addition of CH-acids to nitriles, followed by cyclization to give 9-aminopyrido[1, 2- a ]indoles. Abstract : N -(Propargyl)indole-2-carbonitriles undergo DBU-catalyzed addition of CH-acids to nitriles, followed by cyclization to give 9-aminopyrido[1, 2- a ]indoles. The reaction proceeds through the initial formation of a push–pull enamine, alkyne–allene rearrangement and intramolecular nucleophilic cyclization. Nitromethane and malonate esters can be employed as the CH-acids. The resulting compounds were found to exhibit fluorescence properties.